2018
DOI: 10.1039/c7gc03239k
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating transfer hydrogenation mechanisms in non-catalytic lignin depolymerization

Abstract: A good understanding of the mechanisms for non-catalytic depolymerization of lignin via transfer hydrogenation is essential in order to achieve process optimization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Besides, the production of H 2 from fossil resources could be expensive and unsustainable . The catalytic hydrogenolysis of lignin in hydrogen‐donor solvents (methanol, ethanol, isopropanol) without external hydrogen garnered more attention (Table ) …”
Section: Conventional Approach – Catalytic Depolymerization Of Technimentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the production of H 2 from fossil resources could be expensive and unsustainable . The catalytic hydrogenolysis of lignin in hydrogen‐donor solvents (methanol, ethanol, isopropanol) without external hydrogen garnered more attention (Table ) …”
Section: Conventional Approach – Catalytic Depolymerization Of Technimentioning
confidence: 99%
“…In the desire to minimize lignin condensation, recent works have been focused on non‐catalytic solvolysis of lignin in the presence of formic acid, which has shown to both catalyze the depolymerization and supply hydrogen to stabilize the reactive products and intermediates . Other work also highlighted the important role of carbon monoxide generated from formic acid decomposition during non‐catalytic solvolysis of technical lignins . In the past decade, catalytic oxidative or reductive pathways have been prioritized over non‐catalytic solvolysis for the depolymerization of the lignin.…”
Section: Conventional Approach – Catalytic Depolymerization Of Technimentioning
confidence: 99%
“…The relative results are shown in Table 2, where, when the ratio of methanol and raw bio-oil increased, the yield of liquid products decreased slightly, which might be related to some low-molecular weight components of bio-oil being converted to gaseous products under 240 • C. Although there is no obvious difference in the liquid product yield and char among different methanol/bio-oil weight ratios, the components were very different between raw bio-oil and the esterification products, especially the content change in alcohols, acids, esters and ketones and aldehydes; after esterification, the unstable components (acids, ketones and aldehydes) significantly decreased, while the alcohols and esters were remarkably increased (Table 3). These stable components are suitable for hydrogenation at mild conditions [30]. Meanwhile, the low char yields at different methanol/bio-oil mass ratios under 240 • C are mainly attributed to the esterification to reduce the unstable functional groups that led to polymerization and/or coking [30,31].…”
Section: Two Steps Of Esterification and Hydrogenation Over Raney Ni Catalystmentioning
confidence: 99%
“…30 However, the grasses lignin-type peak assignments are in accordance with previously reported studies. 30,31 When the unreacted (light) and reacted (dark) particles FTIR spectra were compared with the HD-BS alkali lignin and Sigmacell cellulose ( Figure 6), only characteristic IR bands of the lignin were maintained from the reacted (black) particles while the unreacted (light) particles still showed characteristic IR bands of the cellulose. As seen in figure 5, the higher number of darker particles for HD-BS with 89wt% DM suggested that lower water content slightly increased the carbonisation of the glucan.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…The 13C-1H HSQC NMR spectra were acquired at 398 K using a Bruker Avance-700 MHz instrument equipped with a 5 mm inverse gradient 1 H/ 13 C cryoprobe using the q_hsqcetgp pulse program (ns = 64, ds = 16, number of increments = 256, d1 =5.0 s). 31 Chemical shifts were referenced to the central DMSO peak (δC/δH 39.5/2.5 ppm). Assignment of the HSQC spectra is described elsewhere.…”
Section: Gc/ms Qualitative Analysismentioning
confidence: 99%